Importance of involving patients and public in health research in Bangladesh and Nepal. (5th November 2020) - Simkhada, Bibha; van Teijlingen, Edwin; Naheed, Aliya; Warren, Angela; Green, Sue
Abstract: Patient and public involvement/engagement (PPI/E) in public health research and health technology assessment (HTA) in high-income countries (HICs) have significantly increased over the past decade. PPI/E helps to improve research and HTA, ultimately benefitting patients and service users. PPI/E is a very new concept in many low- and middle-income countries (LMICs). This paper considers the importance of PPI in public health research and HTA in the development and implementation of technology in the health sector in South Asia. Currently, in this region, health technology is frequently adopted from HICs without local research and HTA. It also discusses the importance of local co-creation of technology to reflect the needs of users within a culturally appropriate setting. It is important for LMIC-based researchers to understand the potential of PPI/E and how it can contribute to it to improve health care and research, especially perhaps in the era of COVID-19.